N4BP3 Regulates RIG-I-Like Receptor Antiviral Signaling Positively by Targeting Mitochondrial Antiviral Signaling Protein - Wang, Chen; Ling, Ting; Zhong, Ni; Xu, Liang-Guo (Frontiers in Microbiology, 2021)
Mitochondrial antiviral signaling protein (MAVS), an adaptor protein, is activated by RIG-I, which is critical for an effective innate immune response to infection by various RNA viruses. Viral infection causes the RIG-I-like receptor (RLR) to recognize pathogen-derived dsRNA and then becomes activated to promote prion-like aggregation and activation of MAVS. Subsequently, through the recruitment of TRAF proteins, MAVS activates two signaling pathways mediated by TBK1-IRF3 and IKK- NF-κb, respectively, and turns on type I interferon and proinflammatory cytokines. This study discovered that NEDD4 binding protein 3 (N4BP3) is a positive regulator of the RLR signaling pathway by targeting MAVS. Overexpression of N4BP3 promoted virus-induced activation of the interferon-β (IFN-β) promoter and interferon-stimulated response element (ISRE). Further experiments showed that knockdown or knockout N4BP3 impaired RIG-I-like receptor (RLR)-mediated innate immune response, induction of downstream antiviral genes, and cellular antiviral responses. We also detected that N4BP3 could accelerate the interaction between MAVS and TRAF2. Related experiments revealed that N4BP3 could facilitate the ubiquitination modification of MAVS. These findings suggest that N4BP3 is a critical component of the RIG-I-like receptor (RLR)-mediated innate immune response by targeting MAVS, which also provided insight into the mechanisms of innate antiviral responses.